Peningkatan Keterampilan Budidaya Tanaman Organik melalui Pelatihan Pembuatan Pestisida Nabati dan Pupuk Kompos - Fakhrudin, Jaini; Ali, Muhammad; Yama, Danie Indra; Muliani, Muliani; Susana, Susana; Mutaqin, Zaenal; Yunita, Tika Rahma; Delyani, Rista; Ardianti, Nova; Naturindo, Naupal (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The majority of residents in Punggur Kapuas are engaged in farming, primarily in horticulture and food crops, making agriculture a pivotal economic sector in the region. However, a significant issue has been the heavy reliance on chemical pesticides and fertilizers, which not only pose environmental risks but also indicate a lack of knowledge regarding sustainable and eco-friendly farming practices. The continuous use of chemical inputs has led to soil and water pollution, as well as disruptions to the natural ecosystem. To combat these challenges, this initiative focuses on training and educating farmers in the production of natural botanical pesticides and organic compost. The project encompasses needs analysis, collaborative design, outreach and training, monitoring, and financial analysis to compare the costs of natural alternatives with chemical inputs. The training component covers two main aspects: the production of botanical pesticides using readily available natural materials such as papaya leaves and garlic, and the creation of organic compost from organic waste. Compost production has a host of benefits, including improved soil fertility and reduced dependence on harmful chemical fertilizers. The method used is by counseling, discussion and direct practice in the field. The outcomes of this initiative include enhanced knowledge and skills among the farming community in Punggur Kapuas regarding the creation of safe and environmentally friendly botanical pesticides, a reduction in the use of chemical pesticides, increased productivity of organic crops, and heightened awareness of the importance of sustainable farming practices. The project has already demonstrated positive impacts, with participants gaining practical expertise in botanical pesticide and compost production. The initiative aims to encourage the adoption of organic farming practices and environmental sustainability, thereby benefiting the local economy and ecosystem. Future efforts may include extension activities, active mentoring, and supplementary skills training to further advance organic crop cultivation and promote sustainability in local agriculture.